Emerging market economies and the financial crisis: Is there institutional convergence between Europe and Asia? - Herman W. Hoen (OrdnungsPolitisches Portal (OPO), 2013)
It is often stated that globalization makes a smaller world by institutional conver-gence. Economic orders become alike across the world. This article addresses institutional change triggered by the global financial crisis of 2008/2009 and challenges this general conviction of worldwide convergence by comparing developments in emerging markets in Europe and Asia. The rise of emerging markets, both in Eastern Europe and in Asia, entailed encompassing institutional reform. In analysing the extent to which there is institutional convergence, the article follows the approach of Varieties of Capitalism. This approach distinguishes two ideal types of capitalism: a liberal market economy and a coordinated market economy. In liberal market economies, firms are primarily driven by competition, whereas in coordinated market economies firms also coordinate with other actors by strategic interaction. The basic premise is that countries with a specific set of institutions develop institutional complementarities. Therefore, considering institutional change, liberal market economies and coordinated market economies are expected to respond in different ways to external shocks, such as the global financial crisis. Being aware of the pitfalls that the approach suffers from by simply pinpointing countries on a broad continuum, the article argues that the emerging market economies in Europe are on the liberal side of the scale. On top of that, it builds the argument of a tentative convergence towards further liberal institutional design. With respect to emerging markets in Asia, another development is observed. There is converging institutional change towards coordinated market economies characterized with strong state influence and an imperative bureaucracy. The expected convergence in the two groups of emerging market economies in Europe and Asia leads to the conviction of divergence between the groups.
Keywords: 330; Globalization; Institutional Economics; Varieties of Capitalism; Emerging Markets